LAW ENFORCEMENT ON THE MISUSE OF RESIDENCE PERMITS BY FOREIGN NATIONALS (A RESEARCH STUDY AT THE SPECIAL CLASS I IMMIGRATION OFFICE TPI BATAM) - Muhammad Iqbal Saputra; Ramon Nofrial; Bachtiar Simatupang; Erniyanti (CV. RADJA PUBLIKA, 2025)
The increasing number of Foreign Nationals (WNA) entering Indonesia, especially Batam City, which directly borders Singapore and Malaysia, strategically impacts the dynamics of immigration supervision and law enforcement. One of the prominent issues is the misuse of residence permits, which threatens the country’s legal sovereignty and creates social and security problems. This study aims to analyze the legal regulations, the implementation of law enforcement, and the obstacles and solutions in addressing the misuse of residence permits by foreigners, using a case study at the Class I Special Immigration Office TPI Batam. This study employs normative and empirical juridical methods with statutory, sociological, and conceptual approaches. Primary data were obtained through in-depth interviews with immigration officers, foreign nationals, and the surrounding community, while secondary data were examined from legislation, official documents, and academic literature. The analysis was conducted using the Theory of State Sovereignty (Hans Kelsen) as the grand theory, the Legal System Theory (Lawrence M. Friedman) as the middle theory, and the Law Enforcement Theory (Kelling & Moore) as the applied theory. The research findings indicate that although the legal regulations regarding residence permits have been stipulated in Law Number 6 of 2011, their implementation still faces obstacles such as limited human resources, regulatory loopholes, weak technological systems, and low legal awareness among both officials and foreign nationals. Therefore, institutional reform, capacity building of human resources, drafting of more operational technical regulations, and strengthening community-based supervision are needed. Effective law enforcement requires synergy between legal structure, substance, and a consistently applied legal culture.